Toolkit for measuring effective voice and agency of women - Kosec, Katrina; Meinzen-Dick, Ruth S.; Elias, Marlène (CGIAR System Organization, 2024)
Toolkit for measuring effective voice and agency of women in climate-related governance at the individual and group levels.